Rumah Kedai Teck Soon Kee (Rumah Kedai Keluarga Wee), 27 & 28 Jalan Bandar, Kampung Cina, Kuala Terengganu - Engku Azahari Tengku Abdul Aziz; Noor Haslinda Jalal; Nur Malis Musa; Vasumathi Balan; Mohd. Lokman Samsuddin (Skudai : Universiti Teknologi Malaysia, 1999)
Kajian Lukisan Terukur (Jabatan Senibina) - Universiti Teknologi Malaysia, 1999